THE FINANCIAL DISTRESS PREDICTION AND FACTOR AFFECTING TOWARD COAL MINING COMPANY (Empirical Study at Coal MiningCompany Listed on the Indonesia Stock Exchange Year 2014-2017) - JAYAWARDHANA, DIANDRA RENALDY (Jurnal Ilmiah Mahasiswa FEB, 2019)
Thegoal of this study was to testwhetherliquidity, financial leverage, profitability, and activity able to predictfinancial distress in the coal mining sector of Indonesia companies listed in the Indonesia Stock Exchange.Explanatory research is the nature of this research. Secondary data was used and obtained through review of literature including articles, journals and published financial reports and accounts. The study used several financial ratios in financial reports of groups of financially distressed companies and actively sound companies in Indonesia period 2014-2017 with the goal to determine the most significant and reliable ratiosfor predicting financial distress. The sampling technique used purposive sampling and the research instruments were tested using the Goodness of Fit Test, and Wald Statistic Test. The hypothesis extracted withBinary Logistic Regression Model. Like in some previous studies the companies were stated as distressed if the company hasÂ  negative net income for 2 consecutive years. Results of the data analysis from Binary Logistic Regression confirmed that financial leverage, profitability, and activity of the company have a significant effect partially to financial distress. From the wald statistic test results,activitywas found to be the bestratio for determiningfinancial distress. The results from this study can be applied to take corrective actionwhen necessary to minimize company failures. Investors and creditors will also be able avoid placing their resources in financially distressed companies unconsciously. Keywords: liquidity, financial leverage, profitability,activity, financial distressÂ